The Role of Relations with Suppliers in the Creation of Sustainable Supply Chain – Practical Examples - Rudnicka Reichel, Agata (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
There are many factors that may have an influence on the method by which a supply chain is managed and the way the relationships among all its links are developed. Sustainability, as a complex and challenging concept, affects the approach to establishing and maintaining relations, extending their scope and scale. Next to the traditional understanding of relations in a supply chain, additional goals emerge, resulting in both positive effects and challenges which its different links need to face. The concept of sustainability means that a business organisation takes on shared responsibility for the whole supply chain to achieve its long‑term goals. Relationships are an important factor affecting the ability to create and manage a sustainable supply chain. Relationship Management seems to be the basis for the creation of a stable and continuous chain which presents characteristics of maturity. The aim of the article is to introduce the issue of maturity which determines the degree of achievement of sustainable development objectives in a supply chain. A case study based on the author’s own research will be presented.